40th Structures, Structural Dynamics, and Materials Conference and Exhibit 1999
DOI: 10.2514/6.1999-1336
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of discrete-source damage progression in a tensile stiffened composite panel

Abstract: This paper demonstrates the progressive failure analysis capability in NASA Langley's COMET-AR finite element analysis code on a large-scale built-up composite structure. A large-scale five stringer composite panel with a 7-in. long discrete source damage was analyzed from initial loading to final failure including the geometric and material nonlinearities. Predictions using different mesh sizes, different saw cut modeling approaches, and different failure criteria were performed and assessed. All failure pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, first failure appears later in tension tests with pressure addition but is quantitatively š‘‡ š‘š‘Ÿš‘’š‘  š‘ ā„Žš‘’š‘Žš‘Ÿ unclear because of the first failure ambiguity during . š‘‡ š‘š‘Ÿš‘’š‘  š‘”š‘’š‘›š‘  Pressure on notched panels is often associated with membrane stiffening to compute critical energy release rates locally [27]. For the tests run here, no global stiffening effect due to pressure addition was observed (Figure 20).…”
Section: Effect Of Pressurementioning
confidence: 93%
See 1 more Smart Citation
“…However, first failure appears later in tension tests with pressure addition but is quantitatively š‘‡ š‘š‘Ÿš‘’š‘  š‘ ā„Žš‘’š‘Žš‘Ÿ unclear because of the first failure ambiguity during . š‘‡ š‘š‘Ÿš‘’š‘  š‘”š‘’š‘›š‘  Pressure on notched panels is often associated with membrane stiffening to compute critical energy release rates locally [27]. For the tests run here, no global stiffening effect due to pressure addition was observed (Figure 20).…”
Section: Effect Of Pressurementioning
confidence: 93%
“…To the authors' knowledge, only a few publications deal with this large notch issue (from 100 mm) and the question is always considered in association with large stiffened panels [21], [22], [23], [24], [25], [26]. These studies use simple uniaxial loading in tension or compression, while other types of study combine it with internal pressure to be more representative of the in-flight fuselage loading [27], [28], [29], [30]. The study, and especially experimental studies, of the combination of tension, shear and pressure loads on a large notch is original in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the Hashin formulation is based on distinct polynomials associated with the different failure modes. In our 3D problem, we have considered the failure modes mentioned in [30,31], in which ij i, j Ā¼ 1, 2, 3 Ć° ƞis the stress tensor and S ij , Y T , X T , Y C , X C are the material strengths:…”
Section: Failure Criteria Applicationmentioning
confidence: 99%
“…According to this method, one or more of the elastic material properties of a lamina are set to be equal to zero or a small fraction of the original value, once failure is detected. As suggested in [31], although the degradation model belongs to the instantaneous unloading category, a small value for the material properties has been retained in order to avoid difficulties in the nonlinear analysis solution.…”
Section: Materials Property Degradation Rulesmentioning
confidence: 99%
“…Slieght et al [9] developed a progressive failure analysis methodology for predicting the nonlinear response and failure of laminated composite structures. Lotts et al [10] demonstrated the progressive failure analysis capability in NASA Langley's COMET-AR finite element analysis code on a large-scale built-up composite structure. Defect/damage tolerance and fracture of pressurized graphite/epoxy thin composite shells were evaluated via a computational simulation technique incorporated in an integrated computer code, by Chamis and Minnetyan [11].…”
Section: Introductionmentioning
confidence: 99%